A EDUCAÇÃO NUTRICIONAL NO CONTEXTO DAS CULTURAS DA INFÂNCIA - Lívia Bernardes Rodrigues; José Milton Lima; Márcia Regina Canhoto de Lima (Universidade do Oeste Paulista, 2016)
Overweight is the main agent in compromising quality of life in individuals, given that, nowadays, this condition affects children in alarming proportions. From this starting point, this investigation aims at bringing nutritional education into Children's Education in the context of childhood cultures, making it possible for children to participate in this change without having to leave the place where they belong, childhood cultures. This investigation was executed through research-action in order to observe and get to know the children as they are through interaction and observation. Results were derived through participative observation, as well as narratives from the parents. From these results, we conclude that promoting healthy eating habits through childhood cultures is a practice that draws the children's attention, making way for positive possibilities in this area.